Prototipe Robot Penancap Alat Ukur pH Tanah Menggunakan Mikrokontroler Berbasis Otonom - Nawawi, Muhammad; Ikhsan, Akhmad Fauzi; Nurichsan, Irman (Fakultas Teknik Universitas Garut, 2025)
This research designed a prototype of a pH measuring insertion robot based on a microcontroller with a wireless control system. The robot can automatically move to predefined locations using GPS and azimuth calculations from a digital compass sensor. The pH sensor is inserted into the ground using a servo motor at a specific depth. Tests were conducted at several locations to evaluate navigation accuracy and insertion success. The results showed that the robot could reach target coordinates with a deviation of less than 13.5 cm, but the pH sensor insertion failed 100%. The navigation system worked well with stable motor RPM, and the wireless control functioned properly. In conclusion, the robot succeeded in navigation but failed in the automatic sensor insertion process.